A comprehensive review on pharmacology of efflux pumps and their inhibitors in antibiotic resistance - Thakur V.; Uniyal A.; Tiwari V. (My University, 2025)
The potential for the build-up of resistance to a particular antibiotic endangers its therapeutic application over time. In recent decades, antibiotic resistance has become one of the most severe threats to public health. It can be attributed to the relentless and unchecked use of antibiotics in healthcare sectors, cell culture, animal husbandry, and agriculture. Some classic examples of resistance mechanisms employed by bacteria include developing antibiotic degrading enzymes, modifying target sites previously targeted by antibiotics, and developing efflux mechanisms. Studies have shown that while some efflux pumps selectively extrude certain antibiotics, others extrude a structurally diverse class of antibiotics. Such extrusion of a structurally diverse class of antibiotics gives rise to multi-drug resistant (MDR) bacteria. These mechanisms are observed in gram-positive and gram-negative bacteria alike. Therefore, efflux pumps find their place in the list of high-priority targets for the treatment of antibiotic-resistance in bacteria mediated by efflux. Studies showed a significant escalation in bacteria's susceptibility to a particular antibiotic drug when tested with an efflux pump inhibitor (EPI) compared to when it was tested with the antibiotic drug alone. This review discusses the pharmacology, current status, and the future of EPIs in antibiotic resistance. © 2021 Elsevier B.V.